Toward Class AAA LED Large Scale Solar Simulator with Active Cooling System for PV Module Tests - (:unkn) unknown (IEEE Electron Devices Society, 2022)
Solar simulators are significant in testing solar cells and photovoltaic (PV) modules since they provide spectrum and optic characteristics close to natural sunlight. This research introduces two fundamental novelties to the literature on light-emitting diode (LED) light source solar simulators. One of these innovations is designing and developing a solar simulator to achieve I-V characterization on a PV module basis instead of cell-based contrary to the previous studies. For this purpose, a unique board with a modular structure is designed on which the LEDs are positioned. In the research, LEDs of at six different wavelengths are used. Spectral match, spatial nonuniformity, and temporal instability performance criteria tests conducted on the illuminated area is performed based on IEC 60904-9 and ASTM 927E-10 standards. Class AAA was obtained according to the large-scale solar simulator standard specified in ASTM 927E-10. The second novelty the study introduces is developing an active cooling system that can prevent an increase in LED junction temperature when the number of LEDs increases in an LED solar simulator with a wide illuminated area. In addition to the fans, this solution is suggested to prevent any damage to the LEDs during the test, as well as high temperatures from affecting the wavelengths and at the same time achieve 25 °C, one of the standard test conditions. Also, the device dimensions are optimized ergonomically for ease of use. With this system designed and devised, it becomes possible to test commercially available PV modules successfully. The active cooling system minimizes the heating problem and the impact of wavelengths that might invalidate performance criteria classes. © 2011-2012 IEEE.
Keywords: Active cooling system; light-emitting diodes (LEDs); photovoltaic (PV) cells; solar modules; solar simulator spectroradiometers